The symbolic expression of power and religion in the public buildings in Safavid Iran: A conceptual interpretation - Sanianiani, Rafooneh Mokhtarshahi (My University, 2013)
In this paper, the ideologies of Shari'ati and Foucault are used to signify and explore the characteristics of Iranian architecture during the Safavid period (1501-1722) with respect to symbolism regarding religion and power. This study focuses on the architecture of public buildings constructed during the Safavid era. These buildings reflect the Safavid rulers' views of political power and religious beliefs. Applying the ideas of Shari'ati and Foucault through a survey of Safavid architecture yields five characteristics common to Safavid public buildings: 'light-floating buildings', 'horizontality', 'inward-outward flow', 'illusion', and 'contrast and dualism'. Each of these characteristics is symbolic of Safavid beliefs regarding religion and power.
Keywords: Architecture; Foucault; Iran; Political power; Public buildings; Religion; Safavids; Shari'ati